2020
DOI: 10.1007/s00520-020-05645-0
|View full text |Cite
|
Sign up to set email alerts
|

What is known about the role of rural-urban residency in relation to self-management in people affected by cancer who have completed primary treatment? A scoping review

Abstract: Purpose Despite wide acknowledgement of differences in levels of support and health outcomes between urban and rural areas, there is a lack of research that explicitly examines these differences in relation to self-management in people affected by cancer following treatment. This scoping review aimed to map the existing literature that examines self-management in people affected by cancer who were post-treatment from rural and urban areas. Methods Arksey and O'Malley's framework for conducting a scoping review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Despite the increased attention on self‐management from policy makers, 20 academics, 2,21 charities, 22 and health and social care professionals, 23 a recent scoping review identified a lack of research examining whether rural‐urban residence has a significant bearing on an individual's ability to self‐manage following cancer treatment 24 . This research addresses that evidence gap.…”
Section: Introductionmentioning
confidence: 96%
“…Despite the increased attention on self‐management from policy makers, 20 academics, 2,21 charities, 22 and health and social care professionals, 23 a recent scoping review identified a lack of research examining whether rural‐urban residence has a significant bearing on an individual's ability to self‐manage following cancer treatment 24 . This research addresses that evidence gap.…”
Section: Introductionmentioning
confidence: 96%
“…However, as many are delivered face-to-face, their accessibility by rural survivors is limited, and the acceptability of urban-developed survivorship care programs by rural cancer survivors, who are known to have unique values [ 22 ] and different attitudes towards help-seeking [ 23 ], is not well understood. There is also little known about rural cancer survivors’ willingness to engage in self-management strategies designed to improve their quality of life [ 24 ]. Online programs are increasingly being developed to assist cancer survivors with post-treatment quality of life issues such as fear of cancer recurrence and sleep disturbance, but a recent review found that, although rural survivors have much to gain from the delivery of survivorship interventions online, most research is focused on online interventions designed for urban breast cancer survivors in the United States [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This paper reports on the secondary analysis of a primary dataset collected as a component of a wider study [ 31 , 35 , 37 ]. The original study was conducted to explore and compare cancer survivors’ experiences of self-management following treatments in rural and urban areas [ 37 ] and aimed to understand the problems and opportunities presented by cancer survivorship from the points of view of those who experienced it firsthand.…”
Section: Methodsmentioning
confidence: 99%
“…There is a consensus within the extant literature that the provision of healthcare services tends to be poorer in rural areas. The logistical difficulties of providing specialist care to smaller, sparse populations and necessitating long-distance travel to larger towns or cities to receive adequate care; increased costs and a lack of resources; a need for higher staff-to-patient ratios and multidisciplinary input; difficulty accessing information; and poor communication and care coordination have all been identified as salient issues for service delivery [ 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 ]. Consequently, the accessibility to services tends to be lower in rural areas [ 15 , 18 , 19 , 27 , 28 ], and many people rely on informal social support from family and friends rather than formal support [ 19 ].…”
Section: Introductionmentioning
confidence: 99%